2020
DOI: 10.3390/biomedicines8120574
|View full text |Cite
|
Sign up to set email alerts
|

Mutations and Copy Number Alterations in IDH Wild-Type Glioblastomas Are Shaped by Different Oncogenic Mechanisms

Abstract: Little is known about the mutational processes that shape the genetic landscape of gliomas. Numerous mutational processes leave marks on the genome in the form of mutations, copy number alterations, rearrangements or their combinations. To explore gliomagenesis, we hypothesized that gliomas with different underlying oncogenic mechanisms would have differences in the burden of various forms of these genomic alterations. This was an analysis on adult diffuse gliomas, but IDH-mutant gliomas as well as diffuse mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…2). These findings may indicate to variations in oncogenic processes among IDH-mutant astrocytomas [28] Further analysis into the "WT" group revealed a subset of 21 tumours which had 42 genes with their expression inversely correlated with MYC expression. All of these 42 genes had copy number losses and were localized to 19q.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…2). These findings may indicate to variations in oncogenic processes among IDH-mutant astrocytomas [28] Further analysis into the "WT" group revealed a subset of 21 tumours which had 42 genes with their expression inversely correlated with MYC expression. All of these 42 genes had copy number losses and were localized to 19q.…”
Section: Discussionmentioning
confidence: 89%
“…Next, we assessed the associations of these alterations with various genomic instability metrics. These metrics, which we devised and described previously, were used to characterise various aspects of genomic instability, including SNV burden, Insertion/Deletion (InDel) burden, copy-number alteration frequency (wGII: weighted Genomic Instability Index), degree of aneuploidy (CAER: chromosomal arm event ratio), copy-number amplitude, and chromothripsis status [28].…”
Section: Analyses Of Pmn Alterationsmentioning
confidence: 99%
“…PA usually exhibit +1q, −11q and −16q as well as +4q, and generally harbour considerably fewer CNVs than adults 88 . A study looking at the correlation of contributing factors of mutational burden in LGG and HGG showed that CNVs and loss of heterozygosity (LOH) clustered together, distinct from molecular alterations, suggesting that these changes may have a common lineage 89 . Research on CNVs are hence much needed to further our understanding of these alterations and the clinical impact they have on the pathogenesis of pA.…”
Section: Copy Number Variations Of Clinical Relevance In Paediatric A...mentioning
confidence: 99%
“…Mutations in enzymes regulating metabolite flux are implicated in gliomas development, as highlighted by the discovery of isocitrate dehydrogenase 1 (IDH1), in more than 70% of diffusely infiltrating WHO grade II and grade III astrocytic and oligodendroglial gliomas, as well as in a small fraction of glioblastomas (GBM), particularly those that develop from low-grade-gliomas (LGG) [3,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%